SANKSI PIDANA ADAT TERHADAP PELAKU TINDAK PIDANA PERZINAAN DI NAGARI ULAKAN KABUPATEN PADANG PARIAMAN - Nurlida Yenti Arnes Satriani (Normative Jurnal Ilmiah Hukum, 2017)
In the Criminal Code (Penal Code) has been regulated on the act of adultery in Article 284 of the Criminal Code with the threat of imprisonment forever Nine months for men who berith adultery or for women who commit adultery or one of them tied marriage ropes. Although the Criminal Code (Penal Code) applies to all areas in Indonesia, but in everyday life people still apply and obey the customary norms / customary law. Customary norms / customary law are rules that apply to a custom existing in a region. Therefore, each region in Indonesia has customs and habits of each other is not the same precisely because of this unequal society can say that adat is an important element that gives identity to the region concerned. Likewise in West Sumatra also apply Minangkabau custom law, one of Nagari in Minangkabau which still apply customary law or customary sanction is Nagari Ulakan, Padang Pariaman regency.